2022
DOI: 10.3389/fbioe.2022.912497
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Collagen-Based Hydrogel Combined With Electrical Stimulation to Promote Neural Stem Cell Proliferation and Differentiation

Abstract: Injectable biomimetic hydrogels are a promising strategy for enhancing tissue repair after spinal cord injury (SCI) by restoring electrical signals and increasing stem cell differentiation. However, fabricating hydrogels that simultaneously exhibit high electrical conductivities, excellent mechanical properties, and biocompatibility remains a great challenge. In the present study, a collagen-based self-assembling cross-linking polymer network (SCPN) hydrogel containing poly-pyrrole (PPy), which imparted electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Davaa et al [57] transplanted NSCs through a collagen hydrogel to the SCI site in SCI model rats, and the results indicated that the collagen hydrogel protected the NSCs from a severe inflammatory environment, allowing the differentiation of NSCs and recovery of the spinal cord (Figure 3a). Xu et al [89] and Yang et al [86] demonstrated that a collagen hydrogel induces in situ NSCs to form neurons and reduces the accumulation of astrocytes, leading to the recovery of damaged spinal cord tissues. In addition, collagen hydrogels are used to deliver drugs to injury sites.…”
Section: Protein Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Davaa et al [57] transplanted NSCs through a collagen hydrogel to the SCI site in SCI model rats, and the results indicated that the collagen hydrogel protected the NSCs from a severe inflammatory environment, allowing the differentiation of NSCs and recovery of the spinal cord (Figure 3a). Xu et al [89] and Yang et al [86] demonstrated that a collagen hydrogel induces in situ NSCs to form neurons and reduces the accumulation of astrocytes, leading to the recovery of damaged spinal cord tissues. In addition, collagen hydrogels are used to deliver drugs to injury sites.…”
Section: Protein Hydrogelsmentioning
confidence: 99%
“…Xu et al. [ 89 ] and Yang et al [ 86 ] demonstrated that a collagen hydrogel induces in situ NSCs to form neurons and reduces the accumulation of astrocytes, leading to the recovery of damaged spinal cord tissues. In addition, collagen hydrogels are used to deliver drugs to injury sites.…”
Section: Hydrogel‐based Multimodal Strategy For Treating Scimentioning
confidence: 99%
“…[ 12 ] While collagen is normally not conductive, the combination with PPy increased the conductivity to 17.6 S m −1 , which demonstrates advantages of hybrid copolymer formulations. [ 124 ] While the porcine tissue model provides a highly complex environment that properly mimics in vivo sensing conditions, many uncontrollable metabolic mechanisms that can be otherwise readily tuned in cell culture are left unmonitored in tissue samples. As such, the presence of aerobic metabolizing microorganisms that consume glucose in the porcine tissue can alter the readouts, which was indeed confirmed by standard glucose assays, resulting in a sensor viability lifetime of under 5 days.…”
Section: In Situ Sensorsmentioning
confidence: 99%
“…[ 4,5 ] The 3D bioprinted hydrogels with customized structures, intrinsic bioactivity, and biocompatibility provide extracellular matrix (ECM)‐mimetic microenvironments for cell proliferation, migration, and maturation, which have attracted tremendous attention in tissue engineering, disease modeling, drug screening, etc. [ 6–9 ]…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] The 3D bioprinted hydrogels with customized structures, intrinsic bioactivity, and biocompatibility provide extracellular matrix (ECM)-mimetic microenvironments for cell proliferation, migration, and maturation, which have attracted tremendous attention in tissue engineering, disease modeling, drug screening, etc. [6][7][8][9] Recent studies have further revealed the importance of providing electrical cues to the living cells within 3D bioprinted constructs, which can mediate the growth and differentiation of cells for various electroactive tissue repairing applications, e.g., cardiac, skeletal, smooth muscles, and neural tissues. [10][11][12][13] And, electro-conductive biomaterials have been demonstrated to promote the proliferation and differentiation behavior of electrical stimuli-responsive cells, such as neuron cells, [14] bone cells, [15] and muscle cells.…”
Section: Introductionmentioning
confidence: 99%